Reduction of the Fused Filament Fabrication Process Time in the Manufacturing of Printed Circuit Board Slots - Aguilar Duque, Julián Israel; Avelar, Liliana; Balderrama Armendariz, Cesar Omar; Hernandez Arellano, Juan Luis (2020)
Fused Filament Fabrication is an Additive Manufacturing technology that is continuously improving its technologies. The present research exposes the use of the Travel Salesman Problem and Nearest Neighbor Algorithm as a strategy to reduce the time need to print slots shield in a Printed Circuit Board. The methodology used describes the process from the design to the printing board. A board of 98 slots of four geometries was analyzed. The results present a reduction of 5.88% of the original time required to print the board.